Interfacial Distortion of Sb2Te3-Sb2Se3 Multilayers via Atomic Layer Deposition for Enhanced Thermoelectric Properties - Yang, Jun; Daqiqshirazi, Mohammadreza; Ritschel, Tobias; Bahrami, Amin; Lehmann, Sebastian; Wolf, Daniel; Feng, Wen; Pöhl, Almut; Charvot, Jaroslav; Bureš, Filip; Brumme, Thomas; Lubk, Axel; et al. (American Chemical Society, 2024)
Atomic layer deposition (ALD) is an effective technique for depositing thin films with precise control of layer thickness and functional properties. In this work, Sb2Te3-Sb2Se3 nanostructures were synthesized using thermal ALD. A decrease in the Sb2Te3 layer thickness led to the emergence of distinct peaks from the Laue rings, indicative of a highly textured film structure with optimized crystallinity. Density functional theory simulations revealed that carrier redistribution occurs at the interface to establish charge equilibrium. By carefully optimizing the layer thicknesses, we achieved an obvious enhancement in the Seebeck coefficient, reaching a peak figure of merit (zT) value of 0.38 at room temperature. These investigations not only provide strong evidence for the potential of ALD manipulation to improve the electrical performance of metal chalcogenides but also offer valuable insights into achieving high performance in two-dimensional materials.
Mezivrstevné interakce Sb3Te3-Sb2Se3 připraveného technikou depozice atomárních vrstev pro jeho termoelektrické vlastnosti
Keywords: atomic layer deposition; Sb2Te3-Sb2Se3; 2D materials; interface engineering; transport property; depozice atomárních vrstev; Sb2Te3-Sb2Se3; 2D materiály; transportní vlastnosti